Battery Power Management for Portable Devices. - Barsukov, Yevgen (Artech House power engineering series., 2013)
The introduction of Li-ion batteries in 1991 created a tremendous change in the handheld devices landscape. Since then, the energy stored and put to use in palm-sized electronic devices has quadrupled. Devices are continuously getting more power hungry, outpacing battery development. Written by leading engineers in the field, This cutting-edge resource helps you overcome this challenge, offering you an insightful overview and in-depth guide to the many varied areas of battery power management for portable devices. You find the latest details on optimizing charging circuits, developing battery.